„Chainsaw Gutsfuck” – estetyka chaosu w muzyce blackmetalowej - Alicja Sułkowska (Annales Universitatis Paedagogicae Cracoviensis. Studia de Cultura, 2019)
The article analyses the significance of aesthetic and stylistic tropes in the creation of the stage presence of black metal musicians, as well as investigates, from the perspective of media and culture studies, other components associated with the visual side of the genre, such as chaos, nature, violence or the usage of four elements in the construction of the genre atmosphere. Using as an example the bands representing the first and second wave of black metal, along with new proponents of extreme metal stage, the study defines the role of chaos in black metal, specifying its subcategories in terms of discursive usage, allowing to sketch the influence these elements had on the changes and evolution of certain bands’ image. The article aims to present the analogies between visual and factual aspects and black metal-ideology, with special attention being paid to the modern discourses defining today’s condition of the genre.